Skibsstaderne ved Harre Vig – Nye undersøgelser - Bill, Jan; Grimm, Oliver (Kuml, 2002)
The Harre vig boathouses New investigations Medieval and prehistoric boathouses are especially known from Norway, where more than 800 structures from the 1st-16th century have been recorded. They normally appear in the terrain as U-shaped structures, built from stones and/or turf, and with the open end oriented towards a nearby coastline. The medieval constructions tend to be rectangular in plan, while older boathouses have curved sidewalls. Studies of the large boathouses (15-40111 internal length) has demonstrated that throughout time they can be connected to places of administrative importance, in the Middle Ages in terms of the leidang system. Especially in western Norway, there are several examples of historically known leidang-centres – skipreider – that manifests themselves also physically in terms of a Romanesque stone church and a large, medieval boathouse. This reflects the content of medieval Norwegian law, demanding that the leidang ship should be kept in a boathouse, a naust, and that the sail should be kept in a church. Much fewer archaeological boathouses are known from other Scandinavian areas, and in Denmark, only two examples have so far been attested. They both are situated at Harre Vig in northwestern Jutland, on the south side of the Lime Fiord (fig. 1). Harre Vig forms the inner, well-protected part of an inlet cutting into the district Salling on the south coast of the western Lime Fiord. The entrance to Harre Vig is narrow and the two structures were found close to it, on the foreshore beneath a moraine headland facing incoming ships from the Lime Fiord. Thorkild Ramskou from the Danish National Museum undertook the first archaeological investigation of the Harrevig boathouses in 1958. Limiting his excavation to a few trenches in the best preserved, northernmost of the two east-west oriented structures, he failed to produce any kind of dating evidence.The only artefact found was an iron nail of a type usually used in shipbuilding. His conclusions were, that the structures, of which the northern one measured 27.5 m in length and 10.5111 in width (internal dimensions 24x6m) more had the character of sheds with a temporary roofing than actual boat houses (fig. 2). Ramskou proposed that the structures should be seen in relation to gatherings of Danish fleets in the western Lime Fiord in preparations for expeditions to the west. Therefore, he dated the structures to the time before the closing of the western entrance to the fiord, more precisely to the Viking Age or the Early Middle Ages. In spired by the results of Norweg ian boathouse research, and as the result of the Centre’s involvement in a PhD project about Iron Age and Medieval boathouses in Northern Europe by Oliver Grimm, the Centre for Maritime Archaeology at the Danish National Museum in 2000 undertook a renewed investigation of the structures at Harre Vig. The aims were to find material suitable for an archaeological or scientific dating of the structures, as well as to throw more light over their construction. The work was planned and carried out with due respect to the unique character of the two protected monuments, and actual excavations were kept to a minimum (fig. 3). The construction of the walls was studied through a main trench across the structure, continuing in to a slightly elevated area to the north and a cut through the end wall. A cut th rough the seaward end together with one perpendicular to the coast to the north of the structure aimed at confinning that no end wall was hiding in a beach ridge clearly visible in the 3D- model of the site, and thought to be of later date than the structures (fig. 4). Finally, a trench was opened in the interior of the structure, to in vestigate if the presence of any interior wall constructions or roof supports could be demonstrated. Apart from mechanical removal of the turf, all trenches were dug with hand and in planum in order to obtain as much information as possible from the restricted areasexcavated. The trenches through the walls brought about new in formation about their construction, as it was demonstrated that they were partly buildt from material dug up from a trench immediately on theout side of the walls, partly from turf being cut from the close surroundings (fig. 5). The sections established allow for a reconstruction of the walls as between 1.1-1.5 m wide and 1-1.5 m high, probably of trapezoid shape. The cut through the seaward end confirms that there has been no wall construction here, and thus the internal width appears to be 5.6-6.2111 and the opening towards the sea 3.5 m wide. It was not possible to document the presence of any internal constructions, which indicates that a permanent roof may not have been present. Nor were any cultural layer found. The conclusion of Ramskou, that the structures were not boathouses proper, but constituted another type of shelters, probably only in short time use, was thus supported. Shelters without roofs, hróf, are known from Iceland in recent time, where they serve to protect the boats from the wind, rather than from rain and snow. The artefact finds were few. During a metal detector survey, four nail fragments were found, but their contexts were inconclusive. During the excavation six further fragments appeared, mostly from the filling in the northern wall, indicating them to be older than or contemporary to the construction of the wall. One of the fragments was the rove from a rivet, apparently broken up (fig. 6). The size compares to that of a big boat or a small ship, but could also be from a lightly built longship. Its design indicates it to be older than c. 1100. Furthermore five small, magnetic cinders were found, indicating iron working at the site (fig. 7). The possibility exists, however, that they are later intrusions. In the end wall, in a layer, which must have been formed during its construction, remains of a campfire were found. Together with it turned up also 25 small potsherds of what might have been the same globular vessel of local, early 11th century produces. Radiocarbon analyses of three samples of charcoal – one oak, two pine – from the camp fire gave very uniform dating values pointing to the period AD 1020-1040, but with some possibility for a dating in the first half of the 12th century (fig. 8). The dating evidence thus quite uniformly points to a dating around the middle of the l1th century. The dating and the new information on the height of the walls and the possible width of the opening allows us to judge, what kind of ship the shed may have housed. 11th century warships appear to be more slender than their predecessors are and than cargo carriers. The beam of the warships built at the time of the shelter was only 9-14% of their length. This corresponds well to the proportions of the shelter, the opening measuring 15% of the internal length of 24 m. Thus, we may assume that the shed has been able to house a longship of 24 m length, corresponding to 18-20 pairs of oars, or a crew of 40-50 people. The southern structure being similar in proportions to the northern and apparently contemporary, it may have housed a ship of similar size. In what context has it been necessary to keep ships for a highly mobile, amphibious force of up to 100 soldiers at Harre Vig? The nearby village Harre has not only given name to the inlet and other natural landmarks in the vicinity – it has also given name to the local administrative district, herred, although it is situation in the southern end of the district. The herred division can with certainty be related to the leidang from 1140 onwards, but this relationship may be older. Harre herred is known in written sources from 1230 on, Harre village from 1386. The Romanesque church of the village, situated with a wide view over the inlet, indicates the village to be of higher age than its first appearance in historical documents. Slightly unusual is that Harre parish also had another Romanesque church, now only preserved as a ruin (fig. 9). This church was placed close to Harre church, but even closer to the inlet. There are thus some great similarities between the situation known from the Norwegian skipreider with stone churches and large boathouses and that at Harrevig. It is puzzling, however, that the boat sheds at Harrevig are situated at some distance – 1.5 km – from the village (fig. 10).The location is, however, situated as far towards the openin g of the inlet as the landscape allows land transport, and the reason may have been simply to secure rapid deployment of the ships when need arose.That the choice was, after all not a wise one may be indicated by the apparent short time of use for the sheds. Jan Bill & Oliver Grimm Nationalmuseets Marinarkæologiske Forskningscenter